The Intersection of Acute Kidney Injury and Non-Coding RNAs: Inflammation - Li, Bojun; Lin, Fangyou; Xia, Yuqi; Ye, Zehua; Yan, Xinzhou; Song, Baofeng; Yuan, Tianhui; Li, Lei; Zhou, Xiangjun; Yu, Weimin; Cheng, Fan (Frontiers in Physiology, 2022)
Acute renal injury (AKI) is a complex clinical syndrome, involving a series of pathophysiological processes, in which inflammation plays a key role. Identification and verification of gene signatures associated with inflammatory onset and progression are imperative for understanding the molecular mechanisms involved in AKI pathogenesis. Non-coding RNAs (ncRNAs), involved in epigenetic modifications of inflammatory responses, are associated with the aberrant expression of inflammation-related genes in AKI. However, its regulatory role in gene expression involves precise transcriptional regulation mechanisms which have not been fully elucidated in the complex and volatile inflammatory response of AKI. In this study, we systematically review current research on the intrinsic molecular mechanisms of ncRNAs that regulate the inflammatory response in AKI. We aim to provide potential research directions and strategies for developing ncRNA-targeted gene therapies as an intervention for the inflammatory damage in AKI.